2014
DOI: 10.1021/jp5045207
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stable Paramagnetic Nanocomposites Containing Zero-Valence Silver and Copper in a Polymeric Matrix

Abstract: Magnetic properties of perspective nanocomposite materials based on copolymers of 1-vinyl-1,2,4-triazole with acrylonitrile and the formation of zero-valence metallic magnetic nanoparticles were investigated by electron paramagnetic resonance (EPR). In the EPR spectra of the nanocomposites intensive narrow singlets of conducting electrons with g = 2.00 were observed. The shape and width of the signals for silver and copper particles of the nanocomposites depended on microwave power. The Curie law character of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…These numbers are about 3 times larger than the corresponding resonances in the case of semiconductor NCs, such as CdSe (see Supporting Information S2). Possibly, this line broadening results from a different magnetic environment experienced by OlNH 2 when bound to Cu NCs, in agreement with previous reports on paramagnetism in Cu NCs …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These numbers are about 3 times larger than the corresponding resonances in the case of semiconductor NCs, such as CdSe (see Supporting Information S2). Possibly, this line broadening results from a different magnetic environment experienced by OlNH 2 when bound to Cu NCs, in agreement with previous reports on paramagnetism in Cu NCs …”
Section: Resultssupporting
confidence: 92%
“…Possibly, this line broadening results from a different magnetic environment experienced by OlNH 2 when bound to Cu NCs, in agreement with previous reports on paramagnetism in Cu NCs. 27 Despite the pronounced line broadening, the alkene proton resonance 4 remains well resolved, and based on its integrated intensity, we estimated that the sample analyzed here has a surface concentration of bound OlNH 2 of 1.4 nm −2 . As compared to semiconductor NCs, which often have ligand surface concentrations in the range 3.0−5.0 nm −2 , this number is rather low.…”
Section: Chemistry Of Materialsmentioning
confidence: 75%
“…Based upon the EPR characteristics, it can be concluded that the narrow line is a superposition of signals caused by free radicals of the initial matrix and zero-valence silver nanoparticles. This is in good agreement with the EPR data for conductivity electrons of zero-valence metal particles in the nanosystems (such singlets are inherent in the nanoparticles within the range between 1 and 30 nm [24][25][26]). The reduction of silver to zero-valence state most likely occurs due to the oxidable aldehyde and phenol groups [11,12], which are contained in HS in significant amounts.…”
Section: Resultssupporting
confidence: 88%
“…Recently, it has been found that polymers of 1-vinyl-1,2,4-triazole represent a highly effective polymeric stabilizing matrix for metallic nanoparticles, and the nanocomposites obtained show properties of polymer and metal counterparts (hydrophilicity, complex formation ability, chemical thermal stability, biological activity, etc). [4][5][6][7] Also, it has been demonstrated 8 that polymer nanocomposites containing silver nanoparticles (AgNPs) in the poly-1-vinyl-1,2,4-triazole matrix exert antimicrobial activity against Gram-positive and -negative museum and hospital strains, nonfermenting bacteria, and fungi.…”
mentioning
confidence: 99%